2015
DOI: 10.1111/ele.12476
|View full text |Cite
|
Sign up to set email alerts
|

Species colonisation, not competitive exclusion, drives community overdispersion over long‐term succession

Abstract: Ecological communities often transition from phylogenetic and functional clustering to overdispersion over succession as judged by space-for-time substitution studies. Such a pattern has been generally attributed to the increase in competitive exclusion of closely related species with similar traits through time, although colonisation and extinction have rarely been examined. Using 44 years of uninterrupted old-field succession in New Jersey, USA, we confirmed that phylogenetic and functional clustering decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(172 citation statements)
references
References 52 publications
(119 reference statements)
9
161
0
Order By: Relevance
“…In contrast, we observed increased functional clustering of recruiting individuals after the fourth successional year (Figure c,d), suggesting that early successional communities’ recruits increased in functional similarity—a result also observed in a longitudinal study of forest succession in temperate deciduous forests (Li et al., ). This result might be caused by the extinction of recruits that are functionally dissimilar to the species present in these plots (presumably increasing size‐asymmetric light competition, ill‐suited to local conditions or selective predation) or more colonization of tree species that are functionally similar to the residents (Li et al., ). In the first 4 years, the functional local dispersion of recruiting individuals was quite random and then changed to being clustered.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, we observed increased functional clustering of recruiting individuals after the fourth successional year (Figure c,d), suggesting that early successional communities’ recruits increased in functional similarity—a result also observed in a longitudinal study of forest succession in temperate deciduous forests (Li et al., ). This result might be caused by the extinction of recruits that are functionally dissimilar to the species present in these plots (presumably increasing size‐asymmetric light competition, ill‐suited to local conditions or selective predation) or more colonization of tree species that are functionally similar to the residents (Li et al., ). In the first 4 years, the functional local dispersion of recruiting individuals was quite random and then changed to being clustered.…”
Section: Discussionsupporting
confidence: 78%
“…Despite the overall increase in diversity (Figure ), the recruiting individuals were more related to each other than expected from random assembly during early succession (Figure a,b). Previous studies have also shown that early successional communities tend to be composed of ecological similar or closely related species (Letcher et al., ; Li et al., ; Mo et al., ; Norden et al, ; Purschke et al., ; Whitfeld et al., ). In contrast, we observed increased functional clustering of recruiting individuals after the fourth successional year (Figure c,d), suggesting that early successional communities’ recruits increased in functional similarity—a result also observed in a longitudinal study of forest succession in temperate deciduous forests (Li et al., ).…”
Section: Discussionmentioning
confidence: 94%
“…These benefits of phylogenetics would be especially insightful when there are high colonization (Li et al . ) and extinction rates of species from the regional species pool over a sustained restoration period (Barber et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…We also used the same gene sequences of a species that diverged early in seed plant evolution – Cycas revoluta – to serve as the outgroup (Li et al . ; Fig. S1).…”
Section: Methodsmentioning
confidence: 97%
“…Most studies exploring temporal patterns of community assembly mechanisms analyze interannual changes. Through the use of permanent plots analyzed over 44 yr, it was recently shown that decreases in phylogenetic and functional clustering in late successional stages result from colonization dynamics rather than the loss of closely related species (Li et al 2015). Through the use of permanent plots analyzed over 44 yr, it was recently shown that decreases in phylogenetic and functional clustering in late successional stages result from colonization dynamics rather than the loss of closely related species (Li et al 2015).…”
mentioning
confidence: 99%